Religious Communities and Tolerance: Essential Foundations for Creating a Peaceful and Harmonious Society - Ainayya Husna; Meyniar Albina (MAQOLAT: Journal of Islamic Studies, 2025)
Religious tolerance is a crucial element in creating harmony within multicultural societies. This article analyzes the concept of religious tolerance through a literature review, covering its definition, foundations, objectives, benefits, challenges, and strategies for strengthening it. Tolerance is defined as an attitude of respecting differences without imposing personal beliefs, rooted in moral religious values and human rights principles. Its objectives include maintaining social stability, diversity, and social cohesion, with benefits such as strengthened social relationships and the protection of human rights. However, challenges like radicalism, social polarization, and a lack of pluralism understanding remain obstacles. To address these, strategies such as multicultural education, interfaith dialogue, media involvement, and regulations protecting religious freedom are necessary. Using a qualitative approach with thematic analysis of scientific literature, this article provides a comprehensive insight into the importance of religious tolerance in maintaining social harmony while offering practical solutions to strengthen tolerance in diverse societies.